Identity Crisis - Meltzer, Brad and Morales, Rags (Burbank DC Comics)
When the wife of superhero Elongated Man is murdered in her own home, superheroes join forces to scour the country for clues and suspects, while five champions stay behind to protect a secret that could change the world forever.
Include Color Illustrations
Keywords: Justice League of America (Fictitious characters) -- Murder--Investigation and Superheroes -- Heroes -- Graphic novels